Relationship between absence of endocervical cells and negative Pap smears in patients with squamous premalignant cervix lesions - Centeno-Díaz, Roger (2023)
Objective: To determine the relationship between absence of endocervical cells and false negative Pap smears in patients with squamous premalignant cervix lesions. Methods: A cross sectional study was carried out at Servicio de Anatomía Patológica del Hospital General de Huacho. A search for positive cervix biopsies for squamous intraepithelial lesions and their Pap smears from 2016 to 2018 was done. Negative Pap smears with absence of endocervical cells were investigated. Results: 23 out of 158 cytology results showed absence of endocervical cells, only two (8.7%) were reported negative. Eleven cytologies were negative (7%). Conclusions: No relationship was found between absence of endocervical cells and false negative results at Pap smears. Therefore, no influence in the detection of squamous pre-malignant cells was found.